Identification of Thraustochytrids from Mangrove Forest of Tidung Island, Kepulauan Seribu, Jakarta - An Nisaa, Ranti; Hutari, Andri; Awaliah, Walidah; Permatasari, Renna; Ar Rasyid, Muhammad Luqman (Jurnal Biologi Tropis, 2025)
Thrautochytrids are often called heterotrophic microalgae that have a lot of omega-3 docosahexaenoic acid, or DHA. These microbes are found in many mangrove forest areas, including Indonesia, which has the biggest mangrove forests in the world. Indonesia is also beginning to look for useful microbes in these environments. The goal of this study was to find and identify a type of Thrautochytrid called Aurantiochytrium sp. in the mangrove forests of Tidung Island, part of the Thousand Islands near Jakarta. This area has never been studied for this type of microbe before. The study found two isolates of Thrautochytrids, named Aurantiochytrium sp. PTD5 and PTD6. These were identified by looking at the phylogenetic tree made from 18S rRNA sequences. The phylogenetic tree shows that PTD5 and PTD6 are closely related to other Aurantiochytrium strains like SR21 and BL10, which are widely used in research for making omega-3 DHA lipids.